PENELITIAN KERUSAKAN UNIT LAPIS LINDUNG PEMECAH GELOMBANG TERHADAP BERBAGAI SPEKTRUM GELOMBANG - Sriyana, Sriyana; Hadihardaja, Iwan K. (MEDIA KOMUNIKASI TEKNIK SIPIL, 2007)
Determination of the amount of damage in the armour layer unit of breakwater is highly affected by wave spectrum generated. This research is aimed at knowing the influence of many kind of wave spectrum toward the amount of damage in the armour layer unit. This study is carried out by means of irregular non-breaker waves on physical modeling. The spectrums used on irregular waves are Pierson Moskowitz, Bretschneider, Jonswap, and Darbyshire, employing tetrapod, cubes, and rubble mound as the armour layer. The result of the test model indicate that Darbyshire spectrum have largest potential to destroy the stability of armour layer more than spectrum Jonswap, Pierson Moskowitz, Bretschneider.